2008
DOI: 10.1186/1472-6920-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Quality gap of educational services in viewpoints of students in Hormozgan University of medical sciences

Abstract: Background: Higher education is growing fast and every day it becomes more and more exposed to globalization processes. The aim of this study was to determine the quality gap of educational services by using a modified SERVQUAL instrument among students in Hormozgan University of Medical Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 15 publications
8
45
2
3
Order By: Relevance
“…In this study the greatest negative gap between items was observed in item 25 (Visual appealing and comfort of physical facilities) and item 24 has the least negative gap (-0.11) that shows faculty members and staff have partly arranged and professional appearance. Also Kebriaei (6) and Aghamolaei (7) observed that item 25 has the greatest negative gap between all items. Aghamolaei (7) observed that item 24 have the least negative gap between all the items, but in Kebriaei (6) study, item 20 has the least negative gap.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study the greatest negative gap between items was observed in item 25 (Visual appealing and comfort of physical facilities) and item 24 has the least negative gap (-0.11) that shows faculty members and staff have partly arranged and professional appearance. Also Kebriaei (6) and Aghamolaei (7) observed that item 25 has the greatest negative gap between all items. Aghamolaei (7) observed that item 24 have the least negative gap between all the items, but in Kebriaei (6) study, item 20 has the least negative gap.…”
Section: Discussionmentioning
confidence: 98%
“…Also Kebriaei (6) and Aghamolaei (7) observed that item 25 has the greatest negative gap between all items. Aghamolaei (7) observed that item 24 have the least negative gap between all the items, but in Kebriaei (6) study, item 20 has the least negative gap.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Parasuraman, Zeithaml and Berry simplified the gaps model to develop a service qualities scale with five dimensions in 1988, and in 1991 they reworded the negative valence questions into positivevalence questions to make the final version of the ServQual scale [1] . The ServQual questionnaire tool has been widely applied to measure performance in the service industries, including medical services at hospitals worldwide [1][2][3][4][5][6][7][8][9][10][11][12]. The ServQual tool asks for respondents perceptions of service quality with multiple questions under five headings (dimensions) as follows: (1) Tangibility-things perceived by the five human senses; (2) Reliability-consistent performance, free of non-compliance; (3) Responsiveness-prompt and efficient voluntary response to requirements; (4) Assurance-ability of employees to convey trust; (5) Empathy-provision of sensitive individualized care by the organization [10] .…”
Section: Introductionmentioning
confidence: 99%
“…By defining the gap in quality of services, programs can be developed for promoting the quality of education (2). The results of several studies conducted among the Iranian medical students showed that there is a gap in all five dimensions of quality of educational services (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Similar studies carried out among some universities outside Iran have also reported a gap in all dimensions (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%